Team communication strategies of the Phoenix Team Leader of Unlimited Network of Opportunites (UNO) Davao Motivating Sales Force - Castro, Katrina Angela C.
Unlimited Network of Opportunities (UNO), Inc.) is one of the leading network marketing in the country. In line with this, the researcher conducted a study about how their upline leader packages his team communication strategies in order to motivate his sales force/team. The subjects of this study are the Phoenix Upline Team Leader of UNO Davao, Mr. Jowell Mark Lord Rodriguez and his team's core leaders. This study focused on Mr. Rodriguez' team communication strategies, and used these as bases on describing what kind of leadership he exhibits. Through one-on-one interviews and direct observations with the respondents , the researcher found out and concluded that Mr. Rodriguez uses both his personal strategies and UNO's sales strategies in packaging his team communication process in motivating the members of Phoenix Team. The company strategies include the 12 Basic Steps of UNO Business and the ?Copy? Business; and his personal strategies involve communication tools such as trainings/orientations, regular meetings, brochures and audio-visual presentations. From this, the motivating factors used b Mr. Rodriguez in gaining more and better sale force were specified. The researcher also observed that he uses referent power and democratic style of leadership to motivate members and prospects